Injection of human umbilical cord mesenchymal stem cells exosomes for the treatment of knee osteoarthritis: from preclinical to clinical research - Yuzhong Wang; Yajie Kong; Jiejie Du; Lifei Qi; Meiling Liu; Siyi Xie; Jianghui Hao; Ming Li; Shuxing Cao; Huixian Cui; Aijing Liu; Jun Ma; et al. (Journal of Translational Medicine)
Abstract Background Background: Exosomes (Exos) derived from mesenchymal stem cells (MSCs) share similar biological functions with MSCs but are more stable under various pathophysiological conditions, with a lower risk of immune rejection. Human umbilical cord mesenchymal stem cells (hUC-MSCs) are a promising source of MSC-derived exosomes (MSC-Exos), particularly for the treatment of osteoarthritis (OA), a degenerative joint disease characterized by inflammation and cartilage damage. Methods In this study, we conducted in vitro experiments on mouse articular chondrocytes and treated mouse OA models with hUC-MSCs-Exos. To validate the results of hUC-MSCs-Exos in humans, a randomized, double-blind, ascending dose study was conducted to investigate the safety and efficacy of hUC-MSCs-Exos in the treatment of OA, and human chondrocyte toxicity experiments were conducted prior to the clinical trial. Results In this study, we successfully extracted hUC-MSCs and verified their multilineage differentiation ability in different culture media. We then verified the Exos morphology and the expression of CD9, CD63, TSG1, and CALN. In preclinical experiments in vitro and in vivo, we verified that hUC-MSC- Exos can reduce the inflammatory response of articular cartilage and promote its regeneration. Finally, clinical experiments confirmed that hUC-MSC- Exos injection treatment of OA patients did not cause any adverse consequences, and a certain degree of effectiveness was found in the comparison of clinical scores and MRI examinations before and after treatment. Conclusions This study shows that hUC-MSC-derived exosomes effectively reduce inflammation and promote cartilage regeneration in osteoarthritis, with demonstrated safety and efficacy in both preclinical and clinical settings. Trial registration Trial No.MR-13-24-017929. Registered 11 February 2023, https://medicalresearch.org.cn/login# .